Apoptosis after stent implantation compared with balloon angioplasty in rabbits: role of macrophages - Kollum, Marc; Kaiser, Simone; Kinscherf, Ralf; Metz, Jürgen; Kübler, Wolfgang; Hehrlein, Christoph (Arteriosclerosis, thrombosis, and vascular biology, 1997)
Abstract Both cell proliferation and apoptosis (programmed cell death) are supposed to play a role in restenosis after angioplasty. We studied these processes in smooth muscle cells (SMCs) and macrophages 1, 4, and 12 weeks after balloon angioplasty or Palmaz-Schatz stent implantation in rabbit iliac arteries. Proliferating cells were visualized by immunostaining with antibodies directed against proliferating cell nuclear antigen. Apoptotic cells were detected using the TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling) technique, propidium iodide staining, and transmission electron microscopy. At all time points, the neointimal cross-sectional area of the arteries was twofold to fourfold greater after stent implantation than after balloon angioplasty. The total number of neointimal cells was similar 1 and 12 weeks after both interventions. The neointimal cell density, however, decreased by 58% between the 1st and the 12th week after stent implantation compared with a 20% decrease after balloon angioplasty (P<.01). Stent implantation induced more cell proliferation but also more apoptosis in the media than balloon angioplasty after 1 and 4 weeks. In addition, stent implantation caused more macrophage accumulation and apoptosis in the neointima, but cell proliferation rates did not differ significantly in comparison with balloon angioplasty. The higher rate of apoptosis in the neointima 1 week after stent implantation compared with balloon angioplasty is due to an increased rate of SMC and macrophage death. Macrophage accumulation and apoptosis in the early phase after stent implantation appear to play a role in extracellular matrix secretion, which increases neointima formation after 4 and 12 weeks compared with balloon angioplasty in this model.